CHLORIDE-CARBONATE NODULES IN KIMBERLITES FROM THE UDACHNAYA PIPE: ALTERNATIVE APPROACH TO THE EVOLUTION OF KIMBERLITE MAGMAS - Kamenetsky V.S.; Kamenetsky M.B.; Sharygin V.V.; Golovin A.V. (My University, 2006)
In the studying kimberlites, special attention was given to one aspect of the evolution of kimberlite magmas in mantle and crustal conditions: the entrapment of country rocks and interaction with them. Nodules in kimberlites (peridotites, eclogites, metamorphic and sedimentary rocks, as well as diamondiferous rocks) are usually used to estimate physicochemical and structural conditions in the subcontinental lithosphere, the properties of kimberlite magma, and the crystallization conditions of diamonds.
Keywords: Udachnaya pipe